The Capacity Of TNI Medical Organizations In Dealing With Biological Threats In Indonesia To Support National Security - Alif Hanugrah Insan Nanda Pratama; Heridadi; Lasmono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Biological threat is one of the threats that can disturb national security. Covid-19 is a form of biological threat that has disrupted national security in Indonesia and even in the world. The TNI has the task of Military Operations Other Than War in dealing with disasters including biological threats. The aim of this study is to analyze the Capacity of TNI Medical Resources in dealing with biological threats to support national security. The method used by researchers in this research is descriptive qualitative. The results of this study show that the TNI's medical resources have good knowledge and skills in dealing with biological threats, even though at the beginning of the pandemic it seemed that they were not ready because Covid 19 is a new emerging disease. The management of the TNI's medical resources is good, this can be seen from the implementation of guidelines and implementation instructions related to military operations other than war that the TNI's medical resources have cooperated well with stakeholders. The decision-making system of the TNI's medical resources is also good because it has a military decision-making process that looks at various task conditions. The decision-making system implemented by TNI medical resources also does not look at who is in charge of military operations other than the war.